2013
DOI: 10.2478/s13386-013-0125-6
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Infrared Radioluminescence dosimetry in K-feldspar

Abstract: Infrared radioluminescence (IRRL) of K-feldspar, detected at peak wavelength of 865 nm, is emerging as a potential geochronometric tool. The present study explores and attempts to optimize the IRRL dating protocols and proposes a revised protocol for estimation of palaeodose. UV light (395 nm; 700 mW/cm 2 ) bleach of 800 s was optimum to remove the trapped charges responsible for IRRL and, reduced the interference of radio-phosphorescence due to prior irradiations. Validation of the proposed protocol was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…However, in K-feldspar, radioluminescence is also observed in the near infrared region, called Infrared Radio Luminescence (IR-RL). IR-RL in K-feldspar is thought to arise from the trapping of free electrons in the conduction band by the same traps that give rise to IRSL (or trap, according to Andersen et al, 2012), resulting in a broad emission peaking at ∼865 nm at room temperature (Trautmann et al, 1999a,b;Krbetschek et al 2000;Trautmann et al 2000;Varma et al, 2013). Since the number of occupied trapping sites increases with ionising radiation dose, the IR-RL intensity decreases as irradiation progresses, as fewer and fewer sites are available for trapping.…”
Section: Infrared Radioluminescence: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in K-feldspar, radioluminescence is also observed in the near infrared region, called Infrared Radio Luminescence (IR-RL). IR-RL in K-feldspar is thought to arise from the trapping of free electrons in the conduction band by the same traps that give rise to IRSL (or trap, according to Andersen et al, 2012), resulting in a broad emission peaking at ∼865 nm at room temperature (Trautmann et al, 1999a,b;Krbetschek et al 2000;Trautmann et al 2000;Varma et al, 2013). Since the number of occupied trapping sites increases with ionising radiation dose, the IR-RL intensity decreases as irradiation progresses, as fewer and fewer sites are available for trapping.…”
Section: Infrared Radioluminescence: Previous Studiesmentioning
confidence: 99%
“…due to thermally induced transfer are not fully understood (e.g., Jain et al, 2015;Tsukamoto et al 2017). Based on excitation spectroscopy, Andersen et al, (2012) demonstrated that the different IRSL and post-IR-IRSL signals resulted from the same trap (henceforth, the principle trap). Trautmann et al (1998Trautmann et al ( , 1999a proposed an alternative measurement method that seems to use the principle trap but does not rely on optical stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…If we assume complete optical RF signal resetting, another possible cause for RF nat > > RF reg signal could be the sensitivity change due to laboratory treatments (bleaching or irradiation or due to both). Schilles and Habermann (2000), Erfurt and Krbetschek (2003a), Varma et al (2013) and Murari et al (2018) have observed IR-RF sensitivity changes in their studies. Erfurt and Krbetschek (2003a) found that it may lead to an equivalent dose deviation of ~3%.…”
Section: Why Is the Rf Nat Signal Elevated For The Naturally Bleached...mentioning
confidence: 91%
“…Later Varma et al (2013) concluded that exposure of 800 s is optimal for resetting the IR-RF signal using the aforementioned UV LED (delivering 700 mW cm -2 ). Frouin et al (2015) systematically compared the bleaching behaviour of monochromatic light and a solar simulator spectrum.…”
Section: Ir-rf Signal Resettingmentioning
confidence: 99%
“…3). Varma et al (2013) reported that although the IR-RF signal of their sample was almost at its saturation level, it did not show significant phosphorescence after bleaching the sample for 800 s. Hence, they concluded that no extra pause is needed and suggested that a delay of 500 s is sufficient to reduce the phosphorescence down to the background level if the bleaching time is less than 800 s. Similarly, Schaarschmidt et al (2019) reported a weak phosphorescence compared to the IR-RF signal and reduced the pause to 900 s for their samples.…”
Section: Phosphorescencementioning
confidence: 99%